1987
DOI: 10.1111/j.2044-8341.1987.tb02725.x
|View full text |Cite
|
Sign up to set email alerts
|

Foetal heart rate and maternal emotional state

Abstract: Forty-five pregnant women rated themselves for hostility, depression and anxiety. Maternal and foetal heart rates were recorded while they listened to a tape through headphones. The foetuses of anxious mothers showed pronounced responses to certain taped stimuli but this effect was not found for mothers with high hostility or depression scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…as measured using a Quest 1700 Precision Impulse Sound Level Meter, and generally varied according to respective natural volumes in the environment~i.e., screams or a jet taking off were generally louder than chirping birds or a whirring fan!. Some studies have attempted to match sound stimuli more precisely for physical properties such as intensity and frequency~e.g., Benson et al, 1987!. Beyond the abovementioned range restriction, matching sound stimuli was not a practical option in the present research, as the primary goal was to use ecologically valid sounds that effectively communicate affect.…”
Section: Materials and Designmentioning
confidence: 97%
“…as measured using a Quest 1700 Precision Impulse Sound Level Meter, and generally varied according to respective natural volumes in the environment~i.e., screams or a jet taking off were generally louder than chirping birds or a whirring fan!. Some studies have attempted to match sound stimuli more precisely for physical properties such as intensity and frequency~e.g., Benson et al, 1987!. Beyond the abovementioned range restriction, matching sound stimuli was not a practical option in the present research, as the primary goal was to use ecologically valid sounds that effectively communicate affect.…”
Section: Materials and Designmentioning
confidence: 97%
“…This includes increased heart rate stress patterns, pulsatility index of the middle cerebral artery [20], disrupted neurobehavioral development [21,22], and altered behavioral reactivity [23][24][25][26]. In newborns, the effects of antenatal stress continue, as evidenced by reduced birth weight, increased risk for prematurity [1,27], and irritability.…”
Section: Developmental Consequences Of Antenatal Maternal Distress Anmentioning
confidence: 99%
“…Several studies reported that increased maternal anxiety or psychosocial stress is associated with hyperactive fetuses and fetal tachycardia [30,31], a sudden fall in fetal heart rate (FHR) followed by over-swing recovery [32,33], significant FHR increases [34], increased fetal motor activity [35], more time in quiet sleep [36], and higher pulsatility index in the fetal middle cerebral artery [37]. Conversely, reduced anxiety or positive emotional states result in decreased fetal breathing and increased body movements [38,39].…”
Section: Gestational Stress Influences Human Fetal Behaviormentioning
confidence: 99%